Risk perceptions and management strategies in a post-disaster landscape of Guatemala: Social conflict as an opportunity to understand disaster - Fernandez, Manuela Teresa (Elsevier, 2021)
This work analyses a post-disaster case study in Guatemala where a large landslide named “Los Chorros” affected several communities and one of the country’s main highways. Risk managers, starting from their own assessment, decided to respond in a way that did not coincide with the interests of the affected population. Local communities assessed the disaster risk situation from a different conception of risk and developed an alternative solution. Competition for priorities and solutions for risk management reveals that disaster risk is a complex and holistic concept, comprised of a large set of components. The first objective of this work was to identify the criteria and components chosen by each actor to define disaster risk and the approaches employed during risk assessment. The second objective concerned the study of strategies deployed by actors to legitimize both their assessment of disaster risk and its treatment. Using interviews and observation of practices it is possible to affirm that the actors consider very varied criteria when defining a risk situation. These criteria are material, symbolic, natural, economic, social and are linked to the types of vulnerabilities that actors face and recognize. Risk management measures depend on the specific arbitrations of each actor and their ability to be recognized as legitimate. The challenge for decision makers is to involve the various stakeholders, integrate the risk perceptions and assessments carried out by each actor and subsequently seek a compromise to determine which actions are the most appropriate in terms of social acceptance and technical validity.